Intrinsic Photoluminescence Emission from Subdomained Graphene Quantum Dots. Issue 26 (6th May 2016) - Yoon, Hyewon; Chang, Yun Hee; Song, Sung Ho; Lee, Eui‐Sup; Jin, Sung Hwan; Park, Chanae; Lee, Jinsup; Kim, Bo Hyun; Kang, Hee Jae; Kim, Yong‐Hyun; Jeon, Seokwoo
Abstract : The photoluminescence (PL) origin of bright blue emission arising from intrinsic states in graphene quantum dots (GQDs) is investigated. The bright PL of intercalatively acquired GQDs is attributed to favorably formed subdomains composed of four to seven carbon hexagons. Random and harsh oxidation which hinders the energetically favorable formation of subdomains causes weak and redshifted PL.